The real cost of low income settlements: experiences in varied spatial contexts within the same municipal boundary - Sahabodien, Raudhiyah (Department of Civil Engineering, 2017)
Introduction: Since 1994, the response to the low income housing backlog in South Africa has been met with the capital grant, targeted at households earning less than R3500 per month. Scholars and policy makers echo the same sentiments that state funded housing and facilities should be located close to economic opportunities and in close proximity to public transportation systems. However, due to the limitations of the grant, low income housing development has been typically been limited to cheap peripheral land where large scale low income housing projects can be rolled out in the form of low density housing developments. In recent years, a growing body of knowledge has found that the provision of state funded housing opportunities on the urban periphery has a significant impact on urban sustainability, particularly the financial sustainability of government. This study aims to add to the body of knowledge pertaining to how the roll out of low income housing in various locations within the same municipal area affects a household's ability to access economic and social opportunities in terms of financial and social costs to the household. Method: The study considers Hessequa Municipality as a case study, with four settlements within the municipality (Slangrivier, Kwanonkuthula, Diepkloof and Melkhoutfontein) used as sub-cases. The four settlements vary greatly in spatial location, population size, history, growth potential and functional role, thus providing a good opportunity to examine the impacts the provision of low income housing by the state within different spatial locations on the lives of households. A case study research approach is applied, using a mix of methods, namely: a review of documents, the mapping of existing facilities, and a survey of 20 households in each of four settlements. Results: The analysis found notable differences between the provision and access to services amongst the four settlements. The study found that that facility provision to low income households varies from settlement to settlement and that a household's perception about whether accessibility to facilities has improved, is relative to the services which households were previously afforded access. It was found that beneficiaries of housing located in close proximity to facilities and employment opportunities incur little or no cost in terms of travelling to facilities. Households with limited access to facilities have to be selective with regard to which member of the household can participate in activities offered in the broader settlement, as otherwise the costs of travel can be very onerous for households. The survey revealed that the opportunity to get a free house far outweighs any inconvenience associated with limited access to social and economic opportunities, with 100% of respondents indicating that they would choose a poorly located free house rather than a rented home in a better location with better access to facilities. In addition, within the context of the four settlements studied, it was found that travel expenses that would ordinarily have been incurred by households travelling to work and school has been found to be carried by employers or subsidised by government, and therefore have less of an impact on household expenditure than I had anticipated. For example, in Slangrivier 50% of the employed are collected for work by their employer and incur no costs for travelling to work. Similarly, the excessive distance travelled to schools, and its consequent burden of cost, is generally not carried by households, as the Department of Education subsidises the transportation of learners to and from school daily. It was found that the use of facilities is influenced by distance, cost, availability and, interestingly, personal preference. Although the provision of facilities across the four settlements is currently uneven, the municipality has created an expectation amongst the public that, over time, facilities will be provided in all settlements, irrespective of their location.